EFFECT OF RESISTANCE TRAINING AND VARIED INTENSITIES OF WEIGHT TRAINING ON VO2 Max AMONG ATHLETES (International Journal of Food and Nutritional Sciences, 2023)
To find out the effect of resistance training and varied intensities of weight training on vo2 max among athletes. The study was formulated as a true random group design, consisting of a pre test and post test. The subjects (n=60) were randomly assigned to three equal groups of twenty men sprinters in each group. The groups were assigned as Experimental Groups I, II and control group respectively. Experimental group I was assigned as Resistance Training (RT) and Experimental group II was assigned as varied weight training (VWT) and control group. The control group was not given any special treatment except of their routine. Pre tests were conducted on VO2 max. The experimental groups participated in their respective training protocols for a period of twelve weeks.The post tests were conducted on the above said dependent variables after the experimental period of twelve weeks for all the three groups. The differences between the initial and final means on selected variables were considered. The obtained data were subjected to statistical treatment using ANCOVA. In all cases 0.05 level was fixed to test the hypothesis set for this study.